Strategi Komunikasi Politik Pemenangan Kepala Daerah - Yohanes De Britto Bimo Triwicaksono; Adi Nugroho (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
This research is motivated by the importance of political communication strategies for winning in regional head elections. The purpose of this study is to determine the political communication strategy in winning the regional head candidate pair. The theory used in this study is the theory of political communication strategy and the descriptions of other supporting theories about political communication strategies. The research method used is descriptive qualitative case study. The data used in this study include primary and secondary data. Primary data is obtained from interviews with seven informants from the Hendri-ita winning post. Meanwhile, secondary data is obtained from journal literature, literature study, and documentation. Data analysis in this study followed the guidelines of the case study research design. The results of this study indicate that the political communication strategy of the regional head candidate pair is carried out by considering the characteristics of the communication components which are communicators, message content, media, communicants, and feedback. Afterwards, through the consideration of the communication. The communication strategy gave the regional head candidate pair victory in the 2020 Semarang regional head election.